Regioselective anti-Silyllithiation of Propargylic Amines - Sato, Tomohiko; Karad, Somnath N.; Shimokawa, Jun; Yorimitsu, Hideki (Synlett, 2023)
The regioselective anti-silyllithiation of propargylic amines is developed to facilitate the efficient synthesis of alkenylsilanes. This reaction generates an alkenyllithium intermediate that is stabilized by the formation of a five-membered cyclic structure through intramolecular coordination of the nitrogen functional group. Upon subsequent treatment with an electrophile, the alkenyllithium intermediate is further functionalized to afford tetrasubstituted allylic amines bearing a β-silicon substituent.
Keywords: silyllithium; alkenylsilane; allylamine; one-pot synthesis; remote stereocontrol